The Impact of R&D Cooperations on Drug Variety Offered on the Market. Evidence from the Pharmaceutical Industry - Tannista Banerjee; Ralph Siebert (Center for Economic Studies and ifo Institute (CESifo), 2014)
Our study puts special attention to the fact that R&D cooperations in the pharmaceutical industry are formed at different stages throughout the drug development process. We study if the timing to engage in R&D cooperations in the pharmaceutical industry has different impacts on the technology and product markets. Using a comprehensive dataset on the pharmaceutical industry, and estimating a heterogeneous treatment effects model (Heckman et al., 2006) our results show that R&D cooperations formed at the early stages increase the number of R&D projects and the number of drugs launched on the product market. Most interestingly, late stage R&D cooperations significantly reduce the number of drugs launched on the market, even though they increased firms' activity in the technology markets. This result highlights the fact that firms re-optimize their drug development portfolio to avoid wasteful duplication and cannibalizing the sales of the jointly developed drug in R&D cooperations. Our study show that firms cooperating in late stage collaborations re-optimize their individual drug development portfolios, which significantly reduces the number of drugs offered on the market.
Keywords: L24; L25; L65; D22; 330; drug development; dynamics; co-development; pharmaceutical industry; product variety; product market competition; Research and Development cooperation